2007
DOI: 10.1097/sla.0b013e3180f61b09
|View full text |Cite
|
Sign up to set email alerts
|

Proving the Effectiveness of Virtual Reality Simulation for Training in Laparoscopic Surgery

Abstract: A proficiency based VR training curriculum shortens the learning curve on real laparoscopic procedures when compared with traditional training methods. This may be a more cost- and time-effective approach, and supports the need for simulator-based practice to be integrated into surgical training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
221
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 400 publications
(234 citation statements)
references
References 28 publications
2
221
0
7
Order By: Relevance
“…GRS and procedure times on both virtual and benchtop knee models is consistently able to differentiate novice and proficient arthroscopists. Furthermore, our results support current literature showing correlation between [3,5] GRS and motion analysis metrics. To date, there are a plethora of arthroscopic training modalities and measures of performance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…GRS and procedure times on both virtual and benchtop knee models is consistently able to differentiate novice and proficient arthroscopists. Furthermore, our results support current literature showing correlation between [3,5] GRS and motion analysis metrics. To date, there are a plethora of arthroscopic training modalities and measures of performance.…”
Section: Discussionsupporting
confidence: 91%
“…2A-B Built-in motion analysis metrics from the virtual simulator were able to distinguish novice and proficient arthroscopists by overall scores and economy of motion, but not in care with soft tissues. The novice group had lower overall scores in the virtual scope (3 ± 2 [95% CI, 2-4] versus 5 ± 3 [95% CI, [3][4][5][6][7][8], p = 0.018), virtual probe (5 ± 2 [95% CI, 3-6] versus 7 ± 1 [95% CI, 6-8], p = 0.009), and virtual loose-body tasks (4 ± 1 [95% CI, 3-5] versus 6 ± 1 [95% CI, [5][6][7], p = 0.001) (Fig. 3A-B Performance on virtual and benchtop models showed strong correlation based on subjective GRS scores and objective motion analysis metrics, suggesting that subjects performed similarly on both models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following training in wet and dry laboratories, several studies have demonstrated improved performance with a significant learning curve [13][14][15][16]. In the current study, the surgeons, in accordance with the Educational Program for LAG at Department of Surgery II, went through an intensive training course consisting of simulator training and at least three sessions of hands-on training with animals, and obtained basic skills by performing laparoscopic cholecystectomies.…”
Section: Discussionmentioning
confidence: 99%